Bacteremias following autologous stem cell transplantation for multiple myeloma: Risk factors and outcomes. Issue 2 (15th February 2019) - Mohan, Meera; Susanibar‐Adaniya, Sandra; Buros, Amy; Crescencio, Juan Carlos Rico; Burgess, Mary J.; Lusardi, Katherine; Davies, Faith; Morgan, Gareth; Vanrhee, Frits; Zangari, Maurizio; Schinke, Carolina; Thanendrarajan, Sharmilan; et al.
Abstract: Background: Autologous stem cell transplantation (ASCT) is a commonly used treatment for multiple myeloma (MM). This retrospective cohort study characterizes the risk factors and outcomes associated with bacteremia following ASCT at a single center. Methods: We conducted a retrospective analysis in subjects who underwent ASCT for multiple myeloma and other malignancies from May 2014 to March 2015 at a single center. The control cohort included all subjects undergoing ASCT in the same time period who did not develop bacteremia. Results: During the study period, 363 ASCTs were completed in 282 discrete patients. Bacteremia was documented in 13% of all transplants. Enterococcus faecium was the most frequent species overall (14/62, 23%). Vancomycin resistance was present in 93% of E faecium isolates. Bacteremia was associated with a significantly decreased survival in patients who received their transplant after the first year of myeloma treatment. Overall survival (OS) was not significantly different in the two cohorts among patients undergoing ASCT within the first year of myeloma treatment. Survival analysis showed a significantly decreased OS in patients who developed Enterococcus bacteremia as compared to the non‐bacteremia cohort. Enterococcal bacteremia was associated with significantly longer duration of neutropenia (mean 14 vs 9.7 days, P  = 0.01), hospitalization (mean 61.7 vs 20.4 days, P  = 0.0006), and higher mortality (69% vs 25%, P  = 0.01) as compared to other bacteremias. Conclusion: We found a high incidence of E faecium and a low incidence of MRSA and Pseudomonas bacteremias following ASCT in our patient population. Survival analysis in our cohort suggests that the effect of underlying disease status and cumulative chemotherapy is critically important in determining outcomes related to bacteremia. Enterococcal bacteremias following ASCT were associated with significantly higher morbidity and mortality than non‐enterococcal bacteremias.